AMT (3‐(2‐aminopropyl)indole) and 5‐IT (5‐(2‐aminopropyl)indole): an analytical challenge and implications for forensic analysis. Issue 3 (5th October 2012) - Elliott, Simon P.; Brandt, Simon D.; Freeman, Sally; Archer, Roland P.
<x xml:space="preserve">Abstract</x> 5‐(2‐Aminopropyl)indole (5‐IT) and 3‐(2‐aminopropyl)indole (α‐methyltryptamine, AMT) are isomeric substances and their differentiation can be a challenge under routine analytical conditions, especially when reference material is unavailable. 5‐IT represents a very recent addition to the battery of new psychoactive substances that are commercially available from online retailers. This report illustrates how subtle differences observed under mass spectral and UV conditions can help to facilitate the differentiation between the two isomers. Analyses included 1 H and 13C NMR, GC‐EI/CI ion trap MS, applications of several U/HPLC‐DAD and HPLC‐MS methods. Investigations currently underway also highlight the confirmation that AMT was detected in a number of fatal intoxications. These findings also demonstrate that there is a potential risk of misidentification when dealing with both substances. Copyright © 2012 John Wiley & Sons, Ltd.